pZHK2, a bi-functional transformation vector, suitable for two step gene targeting - Ulrich Kück; Stefanie Pöggeler (Fungal Genetics Reports, 2004)
Homologous recombination is a prerequisite for the generation of knock out strains by means of DNA-mediated transformation. In filamentous fungi however, the frequency of ectopic integration events is rather high and the actual efficiency of homologous recombination depends upon the length of homologous DNA flanking the transformation marker. Recently, d´Enfert and coworkers (Chaveroche et al., 2000) presented a two-step technology for the integration of a bi-functional zeocin-pyrG cassette into a target sequence of interest using anEscherichia coli strain expressing the phage lambda Red functions. In the resulting recombinant cosmids, the selection marker is flanked by fungal DNA sequences longer than 1 kb, which can be used to transform appropriate fungal recipient strains. For selection of fungal transformants, those workers used the A. nidulanspyrG gene encoding orotidine-5´-monophosphate decarboxylase, which confers prototrophy in appropriate uridine/uracil auxotrophic recipient strains. Here, we describe the novel bi-functional transformation vector pZHK2, which carries in addition to the zeocin resistance gene the hygromycin B phosphotransferase gene often used as a dominant selectable marker gene in fungal recipient strains. The applicability of the vector is demonstrated by generating a ura3- knock out strain from Sordaria macrospora showing auxotrophy.